Design and Calculation of Op-Amp Using 0.35 Micron Technology: Design and Simulation of a CMOS Operational Amplifier Using 0.35 Micron Technology (Journal of Advances and Scholarly Researches in Allied Education, 2011)
In this paper to describe the design of a CMOSoperational amplifier, which is designed to meet certain given specifications.Based on a clear understanding of the specs, the circuit topology of thestandard CMOS operational amplifier was chosen because it was believed thatsuch a design could meet the specs and that the design of such an amplifier isfairly simple. Comparison is drawn between given specifications and result fromcomputer simulations using mentor graphics in the schematic level.  Herewe had taken 0.35um model from AMS. The results are noted to be satisfactory.